Balanced Scorecard Approach in Strategic Decision Making in Development of Executive Clinic Universitas Trisakti Academic Dental Hospital 2023 – 2027 - Meliani, Meliani; Astoeti, Tri Erri; Yusra, Yohana (Jurnal Administrasi Bisnis, 2024)
Strategic planning enables hospitals to anticipate various ever-changing conditions and provides a roadmap, direction, and means to achieve their goals. The Executive Clinic at RSGM-P FKG USAKTI is a comprehensive and professional healthcare provider offering specialized and public services. However, its role as a profit center has experienced a decline during the two-year pandemic. This research aims to revitalize the Executive Clinic as a profit center for RSGM-P FKG USAKTI. The research methodology employed is operational research. The strategic plan development involves three stages: input, matching, and decision stages. The findings from the research indicate that the input stage resulted in the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices with scores of 2.81 and 2.69, respectively. The matching stage utilized the SWOT matrix and IE matrix, recommending the "Hold and Maintain" strategy. The decision stage includes the prioritized strategies, namely, increasing operational hours and enhancing front office services. The identified strategic objectives are to boost revenue, enhance patient satisfaction, capture market opportunities, improve the institution's image, enhance service quality, upgrade the skills of operators, and enhance staff performance.Perencanaan strategis memungkinkan rumah sakit untuk mengantisipasi berbagai macam kondisi yang selalu berubah- ubah serta menyediakan peta perjalanan, arah yang dituju, dan cara untuk mencapainya. Klinik Eksekutif RSGM-P FKG USAKTI merupakan klinik pemberi asuhan yang memberikan pelayanan publik dan spesialis yang komprehensif dan profesional. Kemampuan klinik Eksekutif sebagai profit center mengalami penurunan selama dua tahun pandemi berlangsung. Penelitian ini bertujuan untuk mengembangkan klinik eksekutif agar dapat kembali menjadi profit center untuk RSGM-P FKG USAKTI. Metode penelitian yang digunakan adalah riset operasional. Penyusunan rencana strategi dilakukan melalui tiga tahap, yaitu tahap input, tahap pencocokan, dan tahap keputusan. Hasil penelitian menunjukkan input stage dengan nilai Matriks IFE dan EFE sebesar 2,81 dan 2,69. Matching stage menggunakan Matriks SWOT dan Matriks IE dengan rekomendasi strategi Hold and Maintain. Decision stage meliputi strategi prioritas terpilih yaitu meningkatkan jam operasional dan meningkatkan layanan front office. Tujuan strategi yang ditentukan yaitu meningkatkan pendapatan, meningkatkan kepuasan pasien, menangkap peluang pasar, meningkatkan citra yang baik, meningkatkan kualitas pelayanan, meningkatnya skill operator dan meningkatkan kinerja staff.